Effect of home care services on anxiety in pregnant women facing childbirth: A Quasi-Experimental Study - Uliarta Marbun; Irnawati Irnawati; Lili Purnama Sari; Dahniar Dahniar; Arisna Kadir (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2026)
Introduction: Anxiety during pregnancy, particularly in the third trimester, is a common psychological condition that may adversely affect the childbirth process and maternal well-being. Home care services provide a holistic and continuous approach that integrates education, emotional support, and family involvement, potentially reducing childbirth-related anxiety. However, evidence on the effectiveness of home care in primary health care settings remains limited. This study aimed to examine the effect of home care services on anxiety levels among third-trimester pregnant women facing childbirth. Research Methodology: A quantitative quasi-experimental study with a posttest-only control group design was conducted at Pattingaloang Primary Health Center from June to August 2025. A total of 40 third-trimester pregnant women were selected using accidental sampling and assigned to an intervention group (n = 20) receiving home care services and a control group (n = 20) receiving standard antenatal care. Anxiety levels were measured using a structured questionnaire. Data were analyzed using univariate analysis and the Independent Sample t-test. Results: Most pregnant women in the intervention group were not anxious (85.0%), while the majority in the control group experienced anxiety (75.0%). The mean anxiety score in the intervention group was significantly lower than that in the control group (17.90 ± 4.05 vs. 25.80 ± 5.12; p < 0.001). Conclusion: Home care services significantly reduce anxiety among third-trimester pregnant women facing childbirth. Integrating home care into routine antenatal services may enhance psychological preparedness and maternal well-being.